Natural additive material for desirable dielectric properties of polypyrrole: Limestone - Kilic, Mehmet (ELSEVIER SCIENCE SA, 2020)
In the present study, the Polypyrrole/Limestone (PPy/LS) composites with different LS content varying from 5 wt.% to 20 wt.% were prepared for the first time. The structural, chemical and morphological investigations of the samples were determined by X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR) technique, and Scanning Electron Microscope (SEM), respectively. The chemical content of the LS was also specified by X-Ray Fluorescence (XRF) spectrometer. The complex permittivity components of the samples were measured by impedance analyzer between 1 Hz and 40 MHz frequencies within the 296 K-353 K temperature interval. Additionally, Nyquist plots of the samples were evaluated for determining the grain and grain boundary contributions in the samples. The real parts of the complex conductivity of the samples were also discussed in terms of frequency, temperature and LS additive wt. percentages. The activation energies of the samples were discussed in the context of de conductivity and total conductivities. Additionally, it was determined that the conductivity mechanisms of the samples indicate the Correlated Barrier Hoping model. By the lights of all dielectric results, it was revealed that the real and imaginary components of the complex permittivity along with the conductivity of the samples are very sensitive to LS additive wt. percentage and temperature. Hence, it can be concluded that it is possible to produce very low-cost PPy based composites with controllable permittivity properties.
Keywords: PPy; Limestone; AC electrical properties; Permittivity; CBH model; GRAIN-SIZE; DISPERSION; COMPOSITES; RELAXATION; CONDUCTIVITY; PERFORMANCE; NANOCOMPOSITES; POLARIZATION; TEMPERATURE; Materials Science; Physics; Polymer Science